NILAI KARAKTER DISIPLIN DAN MANDIRI SISWA KELAS 3 MELALUI GERAKAN LITERASI SEKOLAH - Widya Krismon Sri Palupi; Eka Yuliana Sari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2023)
Discipline and independence of students in schools is very necessary in order to support the teaching and learning process in schools to achieve the expected educational goals. One of the ways used by the school to improve student discipline and independence in literacy activities is by implementing the School Literacy Movement program in accordance with government programs. The purpose of this study was to describe the value of the disciplined and independent character of grade 3 students through the GLS at SDN 3 Jabalsari Tulungagung. This research method uses descriptive qualitative method. Methods of data collection using observation, questionnaires and interviews. The results of the analysis of observations, questionnaires and interviews with 16 subjects, it is known that not all students meet all the indicators of discipline and are independent of the implementation of the GLS. Grade 3 students get a very good category on the value of discipline, but the value of discipline in the implementation of the GLS of superior students is found in indicators of good behavior, where students get a percentage of 90%. While the independent indicators in the implementation of the GLS overall students get a good category, but students are superior in indicators of responsibility in each learning activity, which is getting a percentage of 90%.